MODEL PEMBELAJARAN PAIR CHECKS DAN HASIL BELAJAR BAHASA JERMAN SISWA SMA NEGERI 1 AMBON - Laurisye S Salamony; Samuel Jusuf Litualy; Grietje H Kunu (Universitas Pattimura, 2021)
This study aims to determine the effect of using the pair checks learning model on student learning outcomes in German at SMA Negeri 1 Ambon. The sample consisted of 37 students from the 'Cross -Interests XI MIA 1 and XI MIA 2' classes. This study has two variables, namely the learning mode